Analysis of Various Lockout Tagout (LOTO) Devices used in Industrial Safety - Kumar, Sameer; M.Tauseef, S (International Journal of Engineering and Technology, 2018)
Industries have equipment and processes which use hazardous energies like electrical, chemical, gravity, thermal, hydraulics etc. These hazardous energies are handled with utmost precaution and control of these hazardous energies ensures and enhances Safety. Factories Act-India, Occupational Safety and Health Administration, USA(OSHA) and others have defined a very detailed Hazardous Energy Control Program known as Lockout Tagout(LOTO) where these hazardous energies are controlledThese detailed LOTO procedures requires various LOTO devices to control the hazardous energies. These LOTO devices have many varieties (design, sizes, shapes etc.) based on the application.This paper aims to study various LOTO devices used for controlling various hazardous energies like electrical, mechanical, gravity, chemical, hydraulic, thermal, their specifications, application and limitations on a CNC Machining Centre.This will help in identification and use of most appropriate LOTO device for controlling specific hazardous energies. This can be very efficient in safety enhancement and reduction in safety related incidents.Â Â